MAKING STRATEGIC AND TACTICAL SOLUTIONS IN THE TRANSPORT AND LOGISTICS SYSTEM - Oglih, V. V; ShapovalovО. V; Kuzmenko, A. I.; Lesnikova, I. Yu. (Systems and Technologies, 2023)
The authors showed that with the beginning of the war, the development of the enterprises of the motor transport industry jumped from the micro level of the objectives of the economic agent to the level of state problems. We have proven that improving the work of motor transport enterprises is possible only for the introduction of the concept of combination of systemic, cybernetic and synergistic approaches. The results of the analysis of Ukrainian transport enterprises with the use of systemic ideology are given. Understanding the transport and logistics component as an element of the technical and economic system causes the appearance of a positive synergistic effect, creates the basis for the development of the technical component of enterprises and the improvement of economic indicators. The dominant strategic and tactical decision is the formation of effective principles of management of technical and economic systems using the apparatus of mathematical modelling. The authors proposed an algorithm of actions, which consists of formulating the goal of the examination, forming a set of alternative options, and choosing criteria by which the degree of achievement of the goal can be judged. Due to the diversity of the criteria, emphasis was placed on the formation of the expert group and the formulation of the rules for the work of the expert group with the organizers of the examination. We described the main problems that arise during the development of a consolidated solution in the presence of a wide range of various influencing factors. An ordered set of tools is proposed, which is expedient to use in the context of strategic and tactical management, opera- tional management, optimization of transport and logistics processes. The system of models consists of: assessment of the degree of consistency of experts using different methods, in particular: coefficient of variation; Concordation coefficient; the coefficient of rank correlation of the Spirman; Obtaining a quantitative evaluation using an integral performance criterion. The value of the integral criterion for different variants of events for possible alternatives are inputs for the formation of sound proposals. Application of a set of decision-making criteria in conditions of risk and uncertainty will increase the effectiveness of strategic and tactical decisions in the transport and logistics system.